Hambatan Keluarga Merawat Anggota Keluarga dengan Hipertensi di Kelurahan Kolakaasi Kecamatan Latambaga - Bangu Bangu; Heriviyatno Julika Siagian; Tukatman Tukatman; Grace Tedy Tulak (Jurnal Surya Medika (JSM), 2022)
The Healthy Indonesia Program is one of the strategic Ministry of Health programs through a family approach so that Puskesmas can increase the reach of health services in their area through active home visits. One of the targets of the health services provided in the handling of non-communicable diseases, one of which is hypertension. Hypertension is the main cause of cardiovascular disorders. If not treated seriously will cause stroke, heart failure, kidney failure, dementia, acute myocardial infarction, and visual disturbances. If the risk factors for hypertension can be controlled, the incidence of hypertension can actually be prevented. The prevalence of hypertension in Kolakaasi Village from January to December 2020 was 873 sufferers. Various obstacles experienced by families in providing care for a family member who suffers from hypertension are lifestyles that are difficult to eliminate such as excessive salt intake, the habit of consuming meat, smoking, and drinking alcohol. The purpose of this study was to determine the obstacles experienced by families in caring for family members who suffer from hypertension. The method in this study was a qualitative method with a phenomenological approach. The results of the study of factors that hinder families in providing care for family members with hypertension, namely: indifferent attitude to exercise from the penbertia itself, not wanting to take part in health counseling at the Posyandu/Puskesmas, and the habits of the clients themselves which are difficult to eliminate. Conclusion: The client's habits/lifestyles that are difficult to change such as the habit of consuming salty, fried, and meat foods are the main obstacles for families in providing care for family members who suffer from hypertension.